Comparing the responses of grain fed feedlot cattle under moderate heat load and during subsequent recovery with those of feed restricted thermoneutral counterparts: metabolic hormones - Wijffels, G.; Sullivan, M. L.; Stockwell, S.; Briscoe, S.; Anderson, S. T.; Li, Y.; de Melo Costa, C. C. [UNESP]; McCulloch, R.; Olm, J. C.W.; Cawdell-Smith, J.; Gaughan, J. B. (Springer Nature, 2023)
We set out to determine the impact of moderate heat load on the plasma concentrations of a suite of hormones involved in regulating energy metabolism and feed intake. The responses of the thermally challenged (TC) feedlot steers were compared to those of feed restricted thermoneutral (FRTN) steers. Two sequential cohorts of twelve 518 ± 23 kg Black Angus steers on finisher grain ration were housed in climate-controlled rooms (CCR) for 18 days and returned to outdoor pens for 40 days. The TC group was subjected to a diurnal range of 28–35 °C for 7 days (Challenge) but held in thermoneutral conditions beforehand (PreChallenge), and in Recovery (after Challenge). The FRTN group was held in thermoneutral conditions and feed restricted throughout. Blood was collected over the three periods in CCR and two periods in outdoor pens for 40 days (PENS and Late PENS). Plasma concentrations of prolactin, thyroid stimulating hormone, insulin, leptin, adiponectin and thyroxine (T4) were determined during the five periods. Whilst the pituitary hormones were relatively stable, there were differences in plasma leptin, adiponectin and T4 between the two groups during Challenge and Recovery, and occasionally in PENS. The interaction of the plasma hormone concentrations and rumen temperature and DMI were also investigated. Whilst the positive relationship between DMI and leptin was confirmed, we found a strong negative relationship between adiponectin and rumen temperature, and a strong positive relationship between adiponectin and dry matter intake (DMI) in the TC steers only.
Keywords: Adiponectin; Cattle; Hormones; Hyperthermia; Insulin; Leptin; Prolactin